A single step ultrasound-assisted nitrocellulose synthesis from microcrystalline cellulose - Daniel Santos; Gabrielle D. Iop; Cezar A. Bizzi; Paola A. Mello; Marcia F. Mesko; Fernanda P. Balbinot; Erico M.M. Flores (Ultrasonics Sonochemistry, 2021)
Nitrocellulose is a nitrated cellulose polymer with a broad application in industry. Depending on the nitrogen content, this polymer can be used for manufacturing explosives, varnishes, clothes, and films, being considered a product of high value-added. In this work, the use of ultrasound was investigated for the intensification of nitrocellulose synthesis from microcrystalline cellulose. The ultrasound-assisted nitrocellulose synthesis (UANS) was carried out using several ultrasound systems, such as baths and cup horns, allowing the evaluation of the frequency (from 20 to 130 kHz) and delivered power (from 23 to 134 W dm−3) to the reaction medium. The following parameters were evaluated: acid mixture (H2SO4, H3PO4, CH2O2 or CH3COOH with HNO3, 2 to 14.4 mol L−1), ultrasound amplitude (10 to 70%) and reaction time (5 to 50 min). Better nitrocellulose yield (nitrogen content of 12.5% was obtained from 1 g of microcrystalline cellulose employing a cup horn system operating at 20 kHz, 750 W of nominal power with 60% of amplitude, 25 mL of acid solution (13.6 mL of 18.4 mol L−1 H2SO4 + 9.2 mL of 14.4 mol L−1 HNO3 + 2.2 mL H2O), at 30 °C for 30 min. At silent conditions (mechanical stirring ranging from 100 to 500 rpm), the nitrogen content was lower than 11.8% which demonstrate the ultrasound effects for nitrocellulose synthesis.